An Asymmetric Causality Analysis of the Relationship between Government Expenditure and Unemployment in Turkey - Burcu Yürük; Hakan Acaroğlu (Journal of Economy Culture and Society)
The ongoing debates regarding the optimal government expenditure share have been a critical concern of economic policy for many years. Therefore, determining the share of government expenditure in the economy is important in terms of macroeconomic variables. The relationship between unemployment, which is one of the indicated macroeconomic variables, and public sector size is expressed by Abrams (1999) through the Abrams curve hypothesis. According to this hypothesis, large public sector size increases the unemployment rate. In this study, the validity of the Abrams curve hypothesis in Turkey is being analyzed with Hatemi-J’s (2012) asymmetric causality test that considers the cumulative positive–negative changes of series using the 1985–2019 time series data. In the scope of the work, the use of asymmetric causality analysis is valuable for revealing the hidden causality relationship. According to the findings obtained from the analysis, an asymmetrical causality relationship is found between unemployment positive shock and government expenditure positive shock. An impulse-response analysis was applied to determine the direction of the asymmetric causality relationship, revealing that positive shocks of unemployment increase the positive shocks of government expenditure. The results reveal that the Abrams curve hypothesis is invalid. Therefore, the financial burden of government expenditure in fighting against unemployment should be reduced. Active employment policies aimed at creating employment opportunities should be prioritized for permanently reducing unemployment.